Real world use of T3 to alleviate symptoms of hypothyroidism during preparation of radioactive iodine ablation: experts viewpoint - Bhargav, P. R. K.; Manthri, Ranadheer (International Journal of Research in Medical Sciences, 2024)
Thyroid carcinoma is a common endocrine malignancy with most of the cases being diagnosed as differentiated thyroid cancer. Thyroidectomy is the cornerstone of treatment for thyroid carcinoma. Adjuvant therapy with radioactive iodine after surgical resection of all known primary tumor tissue and metastatic foci is advocated. The preparation for radioactive iodine ablation requires elevation of thyroid stimulating hormone to 30 mIU/l for ensuring uptake of I-131 by thyroid follicular cells. In the Indian setting, there are specific challenges in preparation for radioactive iodine ablation including the high cost of recombinant TSH injection which may preclude its use in most patients. The practical approach adopted by Indian endocrinologists, endocrine surgeons and nuclear medicine physicians in the preparation of post-thyroidectomy thyroid cancer patients for radioactive iodine ablation in the real-world setting needs to elaborated and chronicled for providing guidance specific for the constraints encountered in the Indian scenario. Thyroid hormone withdrawal is affected by cessation of levothyroxine for 4 weeks prior to radioactive iodine ablation leading to profound hypothyroidism. This can be addressed by appropriate use of liothyronine (LT3) to substitute levothyroxine after its withdrawal. LT3 administration of 20 mcg twice or thrice a day (40 to 60 mcg/day in divided doses) is the best practice during THW. The duration of LT3 replacement following cessation of levothyroxine, is for 2-3 weeks and then 10-14 days off LT3. These practices are corroborated by evidence from literature and recommendations from guidelines elucidating the use of liothyronine during the period of thyroid hormone withdrawal.